PENGARUH KOMPETENSI, DISIPLIN KERJA DAN BEBAN KERJA TERHADAP KINERJA BERDASARKAN PERSEPSI KARYAWAN PT. BANGUN TEKNIK BAJA BALIKPAPAN - Anhar, Bani; Nainggolan, Hermin; Amanda, Jelisa; Handayani, Lilik (Jurnal GeoEkonomi, 2025)
The purpose of this research is to determine the influence of competency, work discipline and workload on the performance of PT. Bangun Teknik Baja employees. The sampling technique used in this research was method purposive sampling, namely all employees in the welder division, lathe operators, line boring operators and plating operators, totaling 88 (eighty eight) people. The data used in this research is primary data by distributing questionnaires to employees. The data analysis technique used in this research is multiple linear regression analysis assisted by SPSS version 26. The results of this research show that simultaneously competence, work discipline and workload have a significant influence on performance. Partially, competency has a positive and significant effect on employee performance. Partially, work discipline has a positive and significant effect on employee performance. Partially, workload has a negative and insignificant effect on employee performance.